Performance evaluation of cashew gum and gelatin blend for food packaging. (September 2018) - Oliveira, M.A.; Furtado, R.F.; Bastos, M.S.R.; Leitão, R.C.; Benevides, S.D.; Muniz, C.R.; Cheng, H.N.; Biswas, A.
Graphical abstract: Highlights: Interaction intermolecular between the polymers were sufficient to minimizer blend solubility. Cashew gum and gelatin film had the capacity to hinder the water vapor diffusibility. Gelatin addition improved the thermal stability of the CG/G film. The film produced with cashew gum and gelatin is easily biodegradable. Abstract: In this study, a polysaccharide and a protein were combined to form a polyblend that can be used for food packaging. Cashew gum (CG) and gelatin (G) films were generated by the casting method with the help of the central composite rotational design. When filmogenic solutions of 2.5–7.5 g of G and CG were dissolved in 100 mL water with 10% glycerol, the resulting films were compact and homogeneous with no pores present. Different CG/G ratios were examined for water vapor permeability (WVP), thickness, solubility, mechanical and thermal properties, surface morphology, and biodegradability. The results showed that at around 1:1 CG/G weight ratio the solubility decreased, reaching the minimum value at the CG composition of 45%. The blend of 50/50 CG:G showed the best WVP (1.16 g mm k Pa −1 h −1 m −2 ). For elongation at break, the combination of 5 g CG and 2.5 g G provided the best results with over 100% elongation. The films were shown to be easily biodegradable, producing as much CO2 as starch during the 22 days of an aerobic biodegradability test.